2021
DOI: 10.15252/embj.2020106065
|View full text |Cite
|
Sign up to set email alerts
|

5‐Fluorouracil efficacy requires anti‐tumor immunity triggered by cancer‐cell‐intrinsic STING

Abstract: 5‐Fluorouracil (5‐FU) is a widely used chemotherapeutic drug, but the mechanisms underlying 5‐FU efficacy in immunocompetent hosts in vivo remain largely elusive. Through modeling 5‐FU response of murine colon and melanoma tumors, we report that effective reduction of tumor burden by 5‐FU is dependent on anti‐tumor immunity triggered by the activation of cancer‐cell‐intrinsic STING. While the loss of STING does not induce 5‐FU resistance in vitro, effective 5‐FU responsiveness in vivo requires cancer‐cell‐intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 64 publications
1
40
0
Order By: Relevance
“…However, 5-FU has a chemical structure similar to uracil and thymine and interferes with nucleotide synthesis and incorporates into DNA, which may have a mutational impact on both surviving tumor and healthy cells [ 2 ]. Additionally, 5-FU could trigger cancer cell-initiated anti-tumor immunity to reduce the tumor burden, and to improve therapeutic effectiveness for colon and other cancers [ 3 ]. Despite these advances, drug resistance remains a significant limitation to the clinical use of 5-FU [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, 5-FU has a chemical structure similar to uracil and thymine and interferes with nucleotide synthesis and incorporates into DNA, which may have a mutational impact on both surviving tumor and healthy cells [ 2 ]. Additionally, 5-FU could trigger cancer cell-initiated anti-tumor immunity to reduce the tumor burden, and to improve therapeutic effectiveness for colon and other cancers [ 3 ]. Despite these advances, drug resistance remains a significant limitation to the clinical use of 5-FU [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depletion of cellular pyrimidines via genetic intervention or treatment with the pyrimidine nucleoside analogue 5-fluorouracil (5-FU) triggered mtDNA-dependent cGAS-STING activation, demonstrating that this mtDNA release pathway may be of relevance in a number of clinical contexts ( Sprenger et al, 2021 ). For instance, cGAS-STING dependent type I IFN production is triggered by 5-FU in cancer cells and supports effective anti-tumour immunity in colorectal cancer ( Tian et al, 2021 ). Intriguingly, YME1L was found to be frequently mutated in colorectal cancer tissue, which may drive the migration of mtDNA to the nucleus observed in these cancers ( Srinivasainagendra et al, 2017 ).…”
Section: Metabolic Control Of Mtdna-dependent Innate Immunitymentioning
confidence: 99%
“…98,108,117,119 Micronuclei-like DNA structures increased upon 5-FU treatment and the efficacy of 5-FU to reduce tumor burden in murine colorectal cancer models was dependent on STING-mediated anti-tumor immunity. 98 Antilipemic agent lovastatin, served as SHP2 agonist, enhanced the sensitivity of colorectal cancer to DNA damaging drug CPT-11. Exploration of the molecular mechanism indicated that SHP2 inhibited DNA damage repair via dephosphorylating PARP1, thus activating cGAS-STING signaling pathway (Table 3).…”
Section: Targeting Cgas-sting Signaling Pathway In Colorectal Cancermentioning
confidence: 99%